Acetylsalicylic acid reduces cigarette smoke withdrawal-induced anxiety in rats via modulating the expression of NFĸB, GLT-1, and xCT - Hammad, Alaa M.; Alzaghari, Lujain F.; Alfaraj, Malek; Al-Qerem, Walid; Talib, Wamidh H.; Alasmari, Fawaz; Amawi, Haneen; Hall, F. Scott (Frontiers in Pharmacology, 2023)
Background Chronic exposure to cigarette smoke produces neuroinflammation and long-term changes in neurotransmitter systems, especially glutamatergic systems. Objective We examined the effects of cigarette smoke on astroglial glutamate transporters as well as NF-κB expression in mesocorticolimbic brain regions, prefrontal cortex (PFC) and nucleus accumbens (NAc). The behavioral consequences of cigarette smoke exposure were assessed using open field (OF) and light/dark (LD) tests to assess withdrawal-induced anxiety-like behavior. Methods Sprague-Dawley rats were randomly assigned to five experimental groups: a control group exposed only to standard room air, a cigarette smoke exposed group treated with saline vehicle, two cigarette smoke exposed groups treated with aspirin (15mg/kg and 30mg/kg, respectively), and a group treated only with aspirin (30 mg/kg). Cigarette smoke exposure was performed for 2hr/day, 5days/week, for 31days. Behavioral tests were conducted weekly, 24hrs after cigarette smoke exposure, during acute withdrawal. At the end of week4, rats were given either saline or aspirin 45 min before cigarette exposure for 11days. Results Cigarette smoke increased withdrawal-induced anxiety, and 30 mg/kg aspirin attenuated this effect. Cigarette smoke exposure increased the relative mRNA and protein expression of nuclear factor ĸB (NFĸB) in PFC and NAc, and aspirin treatment reversed this effect. Also, cigarette smoke decreased the relative mRNA and protein expression of glutamate transporter1 (GLT-1) and the cystine-glutamate transporter (xCT) in the PFC and the NAc, while aspirin treatment normalized their expression. Conclusion cigarette smoke caused neuroinflammation, alterations in glutamate transporter expression, and increased anxiety-like behavior, and these effects were attenuated by aspirin treatment.